Pelleting corn-soybean meal swine diets - Skoch, E.R.; Binder, S.F.; Deyoe, C.W.; Allee, G.L.; Behnke, Keith C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred forty-six pigs were used to study the effects of steam pelleting a corn-soybean meal diet on pig performance. Treatments included ground meal, meal steam conditioned to 80 C (176 ̊F) before pelleting, meal pelleted without steam conditioning, and a meal diet with 2% molasses replacing corn. Steam-conditioning the meal before pelleting resulted in less starch damage, and less electrical energy was required for pelleting. Pellet durability was considerably increased with steam conditioning. None of the processing methods studied caused significant (P<.05) improvement in daily gain, feed efficiency, or energy digestibility for weanling pigs. A significant improvement (P<.05) over the control diet in feed efficiency and energy digestibility, was found with either pelleting treatment for grower-finisher pigs. However, daily gain was not significantly (P<.05) improved.
Keywords: Swine; Pelleting corn-soybean; Steam pellets; Energy digestibility; Feed efficiency; Daily gain